Neogene ignimbrites and volcanic edifices in southern Peru: Stratigraphy and time-volume-composition relationships - Thouret, Jean-Claude (2008)
In the Central Andes of Peru, four volcanic arcs, termed Tacaza, Lower and Upper Barroso, and Frontal arc, have been active over the past 30 Ma (Fig. 1). They form five units between Moquegua and Nazca (14°30– 17°15’°S and 70–74°W). The ‘Neogene ignimbrites’ (<25 Ma) comprise six generations of widespread sheets (>500 km2 and >20 km3 each), representing a major crustal melting event, triggered by thickening and advective heat input from the mantle wedge. Also, four generations of edifices (i.e shields, composite cones, and dome clusters) and monogenetic fields mostly overly the ignimbrites based on ages, stratigraphy and mapping.